PC Cluster Implementation of a Mass Transport Two-Dimensional Model - Dorneles, Ricardo Vargas; Rizzi, Rogério Luis; Zeferino, Cesar Albenes; Diverio, Tiaraju A.; Navaux, Philippe O. A.; Susin, Altamiro A.; Bampi, Sergio (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2000)
This work presents a parallel solution for the continuity and horizontal momentum equations, and for the mass transport equation. They constitute a model for contaminant transport simulation. The first ones were solved spplying Krylov-Schwarz method and for the last one it was used a pipelined Thomas method. The computational model was implemented on a PC cluster using MPI message passing library. Semi-implicit numerical schemes were developed over a staggered grid.